Analysis of Caffeine Levels in Packaged Coffee in Indonesia - Baehaki, Farhan; Nurhamidah, Yeni; Purwaeni, Purwaeni (Lighthouse Publishing, 2023)
Coffee is a popular and much-loved drink in Indonesian society to relieve drowsiness or increase stamina when working. This is because in coffee, there is an active compound, namely caffeine. Although it has benefits, in fact, caffeine will have a negative impact on the body if consumed in excess. The Indonesian National Standard 01-3542-2004 has determined that the limit value of caffeine content in food and beverages is 0.45–2% w/w. This study aimed to determine the caffeine content of packaged coffee sold in the community using a UV-Vis Spectrophotometer. The results of the analysis showed that 16 of the 20 samples analyzed had caffeine levels in accordance with the provisions of the Indonesian National Standard, while the other 4 samples had caffeine levels above the specified value. Even sample Q has a caffeine content of 7.12% w/w, far above the threshold value. Based on the results of this study, it can be concluded that there are still packaged coffees containing caffeine above the specified threshold value. So, consumers should pay attention to the amount of caffeine consumed so as not to cause a negative impact on their health.